Total nitrogen content in oxisols ulilized for pastures in Central Brazil - Seiffert, Nelson Frederico (Pesquisa Agropecuaria Brasileira, 2014)
Profiles of oxisols "Latossolo Vermelho Escuro", "Latossolo Roxo Álico" and Bruninzen Avermelhado" were sampled for total N content (N) at depths 0,20,50, 100, 150, 200 and 250 cm. The soils showed significant differences (P < 0,01) in the N mean content of profiles and for the content of different depths. The "Bruninzen Avermelhado" soil had the highest mean of N content level in the profile (0,1263%), the "Latossolo Roxo Álico" presented intermediary content levei (0,0613%) and "Latossolo Vermelho Escuro" the lowest level (0,0 183%). The main N concentration in the soils ocurred atO cm and 20cm, decreasing continuously to 250 cm. The N content of surface layer of these soils showed a significant increase (1' < 0,05) in the rainy season cornpared to the dry season levels. "Latossolo Vermelho Escuro", the most abundant type, was evaluated for N changes after clearing and planting Brachiaria decumbens Stapf. There were no significant changes (P < 0,01) in the N content of the profile and in the content of the different depths during three years of pasture utilization, compared to contenta found on as undisturbed adjacente area used a control, with natural vegetations.